Solar Panel Drive Design Based Internet of Things - Freddy Artadima Silaban; Arga Gilang Rolanda; Lukman Medriavin Silalahi; Setiyo Budiyanto (CCIT Journal, 2023)
Indonesia is located on the equator which makes the island irradiated by the sunlight from 10 to 12 hours per day. The use of solar cell panels is generally placed in certain positions without change. For the optimal consumption of solar energy, then we need a system that follows the sun called a solar tracking system. Research the solar tracker automatically moves on an edge 0° - 180° and otherwise. To control or operate solar cells and easier the maintenance process of solar cell panels, then we need a system called IoT (Internet of Things) combine with microcontroller ESP8266 access on the Thingspeak application. The result of this study shows servo motors moved every 1 hour by 20 degrees from 6 am to 5 pm by the solar panels. Equipped with sensors INA219 to know the results of the solar energy that absorbs by the solar cells and shown on the Thingspeak application.